Navigating constitutional amendments between aspiration and under-standing substance - Mohamad Hidayat Muhtar; Andi Bau Mallarangeng; Moh. Arpat Rasyid; Saharuddin Saharuddin (LEGAL BRIEF, 2025)
Constitutional amendments serve as the primary mechanism that guarantees the fundamental law's relevance amidst social, political, and economic changes. In the Indonesian context, this process consistently involves a conflict between public ambitions, representing the collective will, and the need to uphold the consistency and integrity of fundamental values. This research employs a normative juridical method, including philosophical and conceptual analysis, to investigate the interplay between popular desires and the comprehension of content, while also evaluating the possible hazards associated with amendments influenced by transient populist or elitist conservatism. The study's findings indicate that public ambitions provide significant social legitimacy for change; but, without a comprehension of content, modifications may disregard the concept of justice and jeopardize the stability of the legal system. Conversely, a strategy that prioritizes content while neglecting the desires of the populace jeopardizes the constitution's relevance to social reality. The equilibrium of the two necessitates an inclusive deliberative framework, ongoing constitutional education, and the sophistication of political culture. Consequently, seeing the constitution as a collective social compact is essential to ensure that constitutional change transcends immediate political reactions and evolves into a strategic initiative to fortify democracy and achieve real justice.